Patient Perspectives on Engagement in Recovery after Hip Fracture: A Qualitative Study - Joanie Sims-Gould; Sarah Stott-Eveneshen; Lena Fleig; Megan McAllister; Maureen C. Ashe (Journal of Aging Research)
Purpose. To understand older adults’ engagement in their recovery experience and rehabilitation after a fall-related hip fracture. Method. 50 community-dwelling older adults recovering from a recent (3–12 months) hip fracture (32 women, 18 men) participated in telephone interviews using a semistructured format at 6 and 12 months after recruitment into the study. Interviews were conducted as part of a mixed-methods study designed to test the effect of a postoperative hip fracture management program (B4 Clinic). Results. Three substantive themes were identified in the qualitative data: (1) managing expectations; (2) engaging in physical activity; and (3) there is life after fracture. Participants shared valuable insight into how their expectations for their recovery period compared to their lived experience and the role of physical activity in their ability to return to their prefracture activities. Conclusions. Our findings reflect older adults’ expectations for recovery from hip fracture. Encouraging engagement in rehabilitative exercises and addressing expectations prior to hospital discharge may improve patients’ adherence to rehabilitation programs, functional outcomes, and postoperative quality of life. Implications for rehabilitation include the necessity for early and ongoing engagement of rehabilitation professionals.